Contribution of Islamic Figures in the Formulation of Pancasila - Dawani, Dinda Wirly; Nur, Arwansyah; Harahap, Mardian Idris (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to analyze the contribution of Islamic figures in the formulation of Pancasila. This research is qualitative research using the library research model, historical approach, political approach, and figure study. The political approach referred to in this research is a paradigm review that adopts the thoughts of figures, namely the main figures in the research (KH. Agus Salim and KH Wahid Hasyim) and other nationalist groups, both religious and secular. Primary sources in this research refer to writings written by the figure who is the subject of the research, namely the writings of KH. Agus Salim and KH. Wahid Hasyim. The method used in this research is to collect information and review books, literature, notes, and various reports related to the problem at hand. The data analysis techniques used in this research consist of data reduction, data presentation, and drawing conclusions. The results of this research reveal that Pancasila is the foundational philosophy of the Republic of Indonesia, consisting of five principles that guide the nation. While Pancasila itself is not directly derived from Islamic teachings, some Islamic figures have played roles in the formulation and development of the philosophy, especially during Indonesia's struggle for independence. It's important to note that Pancasila aims to be inclusive and is not specific to any particular religious or ideological group. While Pancasila incorporates universal values, including social justice, democracy, and national unity, it has roots in Indonesia's cultural and religious diversity. The influence of Islamic figures during the formulation of Pancasila reflects the collaborative effort to create a philosophy that could serve as a unifying force for the newly independent nation. In conclusion, the contribution of Islamic figures in the formulation of Pancasila is a testament to the inclusive and collaborative spirit that prevailed during Indonesia's struggle for independence. The resulting philosophy seeks to accommodate the nation's religious and cultural diversity while promoting values of justice, unity, and social welfare. The efforts of these Islamic figures have helped shape Indonesia as a nation that values pluralism and tolerance.